Enhancing the Creativity of Students with Disabilities through STEM-Based Science Learning Games - Helmia Tasti Adri; Giuseppe Fabrini; Suwarjono Suwarjono (SITTAH: Journal of Primary Education, 2026)
Inclusive education in primary schools requires accessible, adaptable science learning materials that support students with disabilities' creative thinking. However, the integration of STEM, gamification, and accessibility principles in science learning games for inclusive classrooms remains limited. This study offers a novel approach by developing an accessible STEM-based science learning game to enhance the creativity of students with disabilities in inclusive primary schools. The study aimed to design, develop, and evaluate an accessible STEM-based science learning game integrated with gamification elements. Using a Design-Based Research (DBR) approach, the study involved three phases: needs analysis, prototype development and expert validation, and classroom implementation with refinement. Participants were 24 fourth-grade students, including 6 with disabilities, from an inclusive primary school in Bogor, Indonesia. Data were collected through expert validation sheets, creativity pre- and posttests, questionnaires, observations, and teacher reflections. The developed game, Eco-Rescue STEM Adventure, included STEM problem-solving tasks, gamification features, audio instructions, adaptive difficulty levels, and simplified navigation. Expert validation showed high feasibility (M = 3.71/4.00). Results indicated significant improvement in creative thinking, with a high average gain score (1.41), while student responses highlighted strong engagement and support for creative learning in inclusive science education.